Impact of Growth Sites on the Phenolic Contents and Antioxidant Activities of Three Algerian Mentha Species (M. pulegium L., M. rotundifolia (L.) Huds., and M. spicata L.) - Brahmi, Fatiha; Lounis, Nassima; Mebarakou, Siham; Guendouze, Naima; Yalaoui-Guellal, Drifa; Madani, Khodir; Boulekbache-Makhlouf, Lila; Duez, Pierre (Frontiers in Pharmacology, 2022)
Researches about the effect of environmental agents on the accumulation of phenolic compounds in medicinal plants are required to establish a set of optimal growth conditions. Hence, in this work, we considered the impact of habitat types, soil composition, climatic factors and altitude on the content of phenolics in Mentha species [M. pulegium L. (MP), M. rotundifolia (L.) Huds. (MR) and M. spicata L. (MS)) grown in different regions of Algeria. The phenolic contents and antioxidant activities were analysed using spectrophotometric and HPTLC methods. The harvesting localities differ by their altitudes and climates, but their soils are quite similar, characterized by slight alkalinity, moderate humidity, no-salinity and high levels in organic matter. Both the contents in total phenolics (TPC), total flavonoids (TFC) and rosmarinic acid (RAC), and the antioxidant activities of Mentha samples collected from these Algerian localities are affected by the geographical regions of origin.The samples of MS and MP from the Khemis-Meliana region showed the highest concentration in TPC (MS, 7853 ± 265 mg GAE/100 g DW; MP, 5250 ±191 mg GAE/100 g DW) while in Chemini the MR samples were the richest in these compounds (MR,3568 ± 195 mg GAE /100 g DW). Otherwise, the MP (from Tichy), MR (from Tajboudjth) and MS (from Khemis-Meliana) specimens exhibited the highest levels of TFC and RAC. The antioxidant levels in a total activity test (reduction of phosphomolybdate) appear correlated with the total phenolics contents but this was not the case for the most important ROS scavenging and iron chelating capacities for which the quality of polyphenols is probably more important than their amounts. A principal component analysis (PCA) score plot indicates that all of the Mentha samples can be divided into four groups; these discriminated groups appear comparatively similar in phenolic contents and antioxidant activities. As for the harvest localities, the Mentha samples were divided into four groups in which the phenolic contents and antioxidant activities were comparatively equivalent.